The uses of platelet indices, NLR (Neutrophil to Lymphocyte Ratio) and PLR (Platelet to Lymphocyte Ratio) in the predictive value diagnosis of benign and malignant masses of the parotid gland (Annals of Medical Research, 2021)
Aim: Parotid gland tumors are uncommon in the head and neck surgery practice and difficult to surgically treat. Planning is very important, especially while planning parotid gland surgery, considering the difficulty of revision surgery. In this context, fine-needle aspiration cytology and radiological imaging stand out. However, preoperative diagnosis is sometimes difficult due to the nature of the salivary gland. At this point, additional methods in preoperative diagnosis are questioned. In our study, it was aimed to determine the surgical modality based on the predictive value in parotid benign and malignant masses with inexpensive, fast and easily obtainable platelet indices, NLR (Neutrophil to Lymphocyte Ratio) and PLR (Platelet to Lymphocyte Ratio).Materials and Methods: The data of 236 patients who were operated on with parotid masses between 2010 and 2020 in our clinic were retrospectively analyzed. The data of the patients and the control group were evaluated statistically.Results: A total of 356 participants were included in the study, including 236 patients who had undergone parotid gland surgery and a control group of 120 healthy individuals. When the data of the participants were reviewed, there was no significant difference between the groups in terms of age. In terms of sex, the number of the male patients was significantly higher than the female participants in the group with only parotid benign neoplasia. Based on the collected data, the mean MPV (Mean Platelet Volume) values were mean 9.1548 ± 1.55152 in the parotid cancer patient group (n1), 9.3810 ± 1.57825 in the inpatient group with parotid benign mass (n2) and 10.49250± 1.05314 in the control group (n3). The mean NLR values were found as 3.6395 ± 3.36035 in the parotid cancer patients (n1), 2.0145 ± 1.04293 in the parotid benign masses (n2) and 1.9689 ± 1.54979 in the control group (n3). The mean PDW (Platelet Distribution Width) values were found as 14.1258 ± 2.82536 in the parotid cancer patient group (n1), 14.5220 ±2.69823 in the parotid benign mass group (n2), and 12.5150 ± 2.49953 in the control group (n3).Conclusion: In our study, we observed that the MPV, PDW and NLR values were significantly changed in the parotid gland tumors. We concluded that NLR values may be used effectively, especially in the predictive diagnosis of malignant masses and in planning surgery.
Keywords: Neutrophil to lymphocyte ratio; platelet index; parotid gland surgery; parotid gland tumors; platelet to lymphocyte ratio